Ethnomedicinal plants used by Kani tribals to treat Rheumatism in Kalakad Mundanthurai Tiger Reserve, Tamil Nadu, India - Christopher, Jenipher; Ayyanar, Muniappan (Ethnobotany Research and Applications, 2022)
Background: The search for safe and alternative remedy for rheumatic disorders from herbal resources is increasing nowadays hence the medicinal plants constitute a promising role in modern medication system due to the presence of several bioactive compounds. The people inhabiting in the forest areas are often affected with several skeleton-muscular disorders especially with rhematic problems, hence the present study was undertaken to document the plants used to treat such diseases. Methods: The present study was carried out to document the traditional knowledge of medicinal plants used in treating rheumatism by Kani tribes who live in the KMTR region in the Southern Western Ghats of Tamil Nadu, India. Extensive field studies were conducted in five hamlets of Kani tribes focusing on the plants used in treating rheumatism. The data was collected using questionnaires, interviews and discussions among the traditional practitioners and other people of the hamlet. Results: The present ethnobotanical survey has led to the documentation of 59 species of medicinal plants belonging to 33 families. Of these, 26 species are the major utilized plants while 33 plant species are used in least quantity. Leaves are widely utilized against rheumatic problems. The medicinal formulations are prepared in the form of decoction, paste and powder which are administered topically or orally based on the disease condition. Conclusion: The medicinal plants were documented with the focus on conserving the ethnic knowledge of Kani tribes as documentary evidence for plant-based natural product research. Among the documented plants, Cardiospermum halicacabum, Elettaria cardamomum, Elephantopus scaber, Cymbopogon citratus, Allium cepa, Sida acuta, Pergularia daemia, and Lawsonia inermis were frequently cited and requires further pharmacological studies to develop an effective drug against chronic illnesses. Keywords: Ethnic community, Folk medicine, Rheumatism, Western Ghats